Subordinated debt (Henry Stewart Talks, 2025)
Subordinated debt in capital structure, Senior debt vs equity vs subordinated debt, Capital stack hierarchy & repayment order, Subordinated debt features & risk profile, Uses of subordinated debt in financing, Regulatory treatment (Basel III, Tier 2), Higher returns & risks for subordinated debtholders, Bail-in scenarios & loss given default